1985
DOI: 10.1002/1097-0142(19851215)56:12<2809::aid-cncr2820561217>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

A study to analyze the origin of tumor cells in malignant fibrous histiocytomas a multiparametric characterization

Abstract: To study the derivation of tumor cells of malignant fibrous histiocytomas (MFH), their phenotypical marker profile was investigated and compared with those of malignant histiocytosis (MH) and of different types of soft tissue tumors (STT). The presence of the following markers was investigated: on paraffin sections, alpha-1-antichymotrypsin (ACT); on frozen sections antigens associated with lymphocytes, macrophages and fibroblasts, the enzymes acid phosphatase, nonspecific esterase, and beta-glucuronidase; and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

1987
1987
1999
1999

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…However, they were also reactive with fibrosarcoma and/or fibroblast cell lines and were thus considered no longer specific for monocyte/macrophages (20,48). All MFH cell lines showed immunohistochemical characteristics very similar to those of fibrosarcoma and fibroblast cell lines (48) as reported by several researchers (5,39,40,55). Positive reaction to the antibodies against type I collagen and prolyl hydroxylase, the enzyme which catalyzes the 4-hydroxylation of proline residues in procollagen, indicates that MFH cells have the capacity to produce collagen (48).…”
Section: Immunohistochemistry Of Malignant Fibrous Histiocytomasupporting
confidence: 68%
“…However, they were also reactive with fibrosarcoma and/or fibroblast cell lines and were thus considered no longer specific for monocyte/macrophages (20,48). All MFH cell lines showed immunohistochemical characteristics very similar to those of fibrosarcoma and fibroblast cell lines (48) as reported by several researchers (5,39,40,55). Positive reaction to the antibodies against type I collagen and prolyl hydroxylase, the enzyme which catalyzes the 4-hydroxylation of proline residues in procollagen, indicates that MFH cells have the capacity to produce collagen (48).…”
Section: Immunohistochemistry Of Malignant Fibrous Histiocytomasupporting
confidence: 68%
“…The cell origin of MFH remains controversial, [2][3][4] but it has been assumed to arise either from bone marrow-derived cells of the mononuclear phagocyte system (histiocytes/macrophages) [5][6][7][8][9] or from mesenchymal cells in the local connective tissue (fibroblasts or their precursors). [10][11][12][13][14][15][16][17][18] In view of the fact that MFH does not express the immunophenotype of a true histiocytic neoplasm, recently it has become increasingly more accepted that MFH has little or no relationship to true histiocytic tumors. 19 Takeya et al have demonstrated that the histiocyte-like cells were reactive macrophages in heterotransplantation of human MFH cells using species-specific antimacrophage antibodies.…”
mentioning
confidence: 99%
“…'~~'~~~~~~ In these studies, cultured cells showed no positive reaction to antibodies directed against macrophages/histiocytes. Thus, there have been opinions that MFH cells are not of bone marrow-derived monocyte/macrophage lineage.ro 15,30 ED1 and ED2 are antibodies specific for cells of the monocyte/macrophage lineage in rats3' Parental MT-8 and MT-9 cells reacted to ED1 and ED2 at a low incidence, and MT-R8 and MT-R9 cells showed enhanced expressions for ED1 and ED2. MT-8 and MT-9 cells may be related to rat monocyte/macrophage lineage.…”
Section: Expression Of Both Histiocytic and Myofibroblastic Phenotypementioning
confidence: 99%